Validity and reliability of combining three methods to determine ventilatory threshold - Gaskill, S. E.; Ruby, B. C.; Walker, A. J.; Sanchez, O. A.; Serfass, R. C.; Leon, A. S. (Medicine & Science in Sports & Exercise, 2001)
Purpose: This research was undertaken to validate a combination of methodologies to determine ventilatory threshold (VT). Methods: Three methods were used individually and then combined to determine VT as follows: 1) ventilatory equivalencies, 2) excess CO2 production, and 3) a modified V-slope method. Three groups of participants-endurance athletes (N = 132), healthy, aerobically active adults (N = 31), and healthy, sedentary/low-active adults (N = 22)-were independently evaluated for VT and compared with the criterion standard lactate threshold (LT) defined as the first rise in blood lactate with increasing intensity of exercise. Results: VT and LT were significantly correlated using the combined VT method within each study group (r = 0.98, 0.97, and 0.95, respectively; P < 0.001). Mean VO2 values at VT and LT were not significantly different between the three groups (P > 0.20). The combined method improved the determination rate of VT and reduced the standard deviation of the LT - VT difference by 80-170% over the individual methods. During test-retest procedures VO2lt and VO2vt determined by the combined method met criteria demonstrating further reliability. Conclusion: The combined method to determine VT is valid and reliable across a wide fitness range in healthy individuals and improves the determination rate and accuracy of VT determination over the use of single methods.